The Effect of Healthy Diet on Cognitive Performance Among Healthy Seniors – A Mini Review - Klimova, Blanka; Dziuba, Szymon; Cierniak-Emerych, Anna (Frontiers in Human Neuroscience, 2020)
At present, a healthy diet appears to be one of the suitable strategies in slowing down cognitive decline in the process of ageing. A number of evidence-based studies confirm its efficacy, safety and cost-effectiveness. The aim of this review is to evaluate and describe recent randomized clinical and cohort studies exploring the effect of healthy diet on cognitive performance among healthy seniors, as well as to update the existing information on this research issue. For these reasons, the authors reviewed full-text, peer-reviewed journal articles written in English and available in Web of Science and PubMed between September 2017 and February 2020. Altogether nine original studies were detected. The results indicate that the appropriate dietary patterns and specific nutrients generally have a positive impact on the enhancement of cognitive functions. Furthermore, the findings reveal that these dietary patterns, as well as single nutrients might have a significant effect on specific cognitive domains, such as memory in general, episodic memory, or processing speed. It also seems that a strict adherence to the dietary patterns and a higher diet variety have a more significant effect on the improvement of cognitive functions. More recently, personalized dietary interventions started to be used in delaying cognitive decline among healthy seniors. Therefore, more randomized control trials or N-of-1 trials should be performed in this research area in order to detect the most suitable dietary pattern or nutrients, which would, together with other modifiable lifestyle factors, contribute to the improvement of quality of life of the ageing population.